The relationship between gunshot-residue particle size and Boltzmann distribution - İlker Kara (Oxford University Press, 2020)
Gunshot-residue (GSR) particles usually form spherical structures, have special dimensions, and a composition that consists of burned and partially unburned matter with a 0.5-50-µm diameter (sometimes larger). The GSR particle-size distributions have been argued to be caused by the effects of equilibrium-surface distributions during formation and have not yet been correlated with a theoretical analysis or probability distribution. This study proposes a model to explain the GSR particle-size distribution quantitatively. Based on the data, and, as predicted by our model, the number of GSR particles decreases proportionally to the inverse square of the GSR particle size as the particle size increases. This result occurs because of the abundance of microstructures that are encountered in the GSR particles.